A manifestação das Arboviroses e suas associações aos condicionantes sociais e de saúde no ambiente citadino de Tobias Barreto/SE - Silva, Karolaine Santos (2023)
Arboviruses name a group of diseases that are transmitted to humans by vectors, such as mosquitoes. Among the common arboviruses are: dengue, Chikungunya and Zika, which are endemic and epidemic diseases transmitted by the mosquito Aedes aegypti, mainly in urban environments. These diseases affect the health-disease process of populations through the influence of social, economic and environmental factors, that is, they are correlated with social and health conditions for their permanence and occurrence. The integration of these factors shows that there are several indicators that affect the space-time dynamics of arboviruses. Thus, it was decided to analyze the configuration of arboviruses and the influence of social and health conditions for the occurrence of these diseases in the population of the city of Tobias Barreto/SE. In the territory analyzed, multiple cases of arboviruses are presented annually in the population, which makes it important to carry out studies that corroborate the understanding of the manifestation of these diseases in the population. In order to achieve the proposed objective, the methodology adopted consisted of a bibliographic, cartographic, documentary and field research survey, using the knowledge of Health Geography and Socio-environmental Geography to analyze the data obtained, with the elaboration of graphs, tables, models and mappings about the reality encountered. The results obtained from Sinan/Net, from 2010 to 2020, allow us to conclude that among the arboviruses in the municipality of Tobias Barreto/SE, dengue had the highest number of notified and confirmed cases, with 2,072 confirmed cases. Then, in 2015, notifications of the other two arboviruses appeared. Of these, in the period from 2015 to 2021, Chikungunya registered 18 cases confirmed by laboratory analysis and Zika that presented one case of the disease. Most of the confirmed cases were located in the city and in the Centro neighborhood. This element, which indicates the incompleteness of the data, and which is reinforced by the Rapid Index Survey for Aedes aegypti (LIRAa) tobiense in 2021 and 2022, in which the configuration denotes that the peripheral neighborhoods have the right conditions to develop possible mosquito breeding sites vector. In general, in the city of Tobias Barreto/SE, the social and health conditions expressed by sanitary sewage, garbage collection, water supply, literacy and income, among other factors, led to the conclusion that areas with higher degrees of contracting arboviruses they are located on the outskirts, mainly in clusters located on city edges. In addition, it was found that urban territorial planning and appropriate health actions must be carried out by political actors to make decisions to combat, control and eradicate diseases in order to sensitize social actors and expand their participation.